Preparation of compost using layer droppings with different materials (Bangladesh Journal of Animal Science, 2013)
The experiment was carried out by anaerobic composting with layer droppings (T1), layer droppings with straw (T2), layer droppings with fodder residues (T3) and layer droppings with saw dust (T4) under soil surface to study the suitable method with layer droppings and their nutrient composition. The sample from composted materials was collected at 0, 10, 20 and 30 d for proximate analysis. In 30 d of composting dry matter and organic matter were gradually decreased in every method and which were also differed among the treatments (p